Italian university in Europe: remarks on equivalence of diplomas and freedom of movement within the Union (RT. A Journal on Research Policy and Evaluation, 2015)
In this paper I discuss aspects of the problems arising when a recognition of qualifications for the profession of university professor acquired in foreign states members of the European Union is attempted in Italy. I show that different obstacles still exist to the achievement of the free movement of workers -a fundamental principle of the Union enshrined in article 45 of the Treaty on the functioning of the European Union. In this sense I also comment on the obligation for university professors of Italian university to reside within the municipality of their university.